PERAN BTS TERHADAP KOREAN WAVE DI AMERIKA SERIKAT UNTUK MENINGKATKAN EKONOMI KOREA SELATAN TAHUN 2017-2021 - Pebriansyah, Niko; Fuadi, Ahmad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
BTS, as South Korea's premier boyband, has played an integral role in supporting their country's economic growth. Through their global success, BTS was able to open new doors in the entertainment industry, making a significant contribution to the South Korean economy. Secondary data analysis methods and cultural diplomacy theory are critical foundations in understanding the global impact of BTS. By utilizing available secondary data and integrating cultural diplomacy theory, BTS succeeded in creating deep and sustainable connections with fans around the world, reflecting strong diplomatic efforts. BTS's concert in the United States was not only the peak of their success but also had a big positive impact on South Korea. Through significant economic contributions, such as ticket and merchandise sales, BTS has helped provide a sustainable economic boost. Additionally, their presence on the international stage has shaped South Korea's positive image at the UN, strengthening the country's position as an empowered global player. Keywords: BTS, Korean Wave, United States, Economic Growth, South Korea, Soft Power Diplomacy, Pop Culture, Globalization